Conditions spatiales de la démocratie participative. « Meetings » à Vosloorus (Ekurhuleni, Afrique du Sud) - Philippe Gervais-Lambony (EchoGéo)
Local participatory democracy meetings are supposed to enable citizens to formulate their demands and compile wish-lists of priorities on their own terms. What do the citizens of the new South Africa “participating” in these meetings really want? To what extent this form of neighbourhood participation is merely a democratic façade, a pretext to incite residents to formulate what is expected, that is a set of predictable requests, neither controversial nor outrageous, but rather tame and placid thus conforming to the rhetoric of consultation? Many writers have commented on this dubious process and some suggest contrasting these official meetings with more spontaneous ones that spring up from people’s own initiative. This dichotomy between invited and invented spaces of participation (Cornwall, 2004 ; Miraftab F, 2004) is discussed here on the base of empirical observation of meetings and taking into consideration “spaces” in the double sense of physical space and social space of interaction. The paper is based on field work conducted from 1999 to 2010 in the township of Vosloorus (located in the Metropolitan Authority of Ekurhuleni in the province of Gauteng).